Investing in Early Childhood Development : Essential Interventions, Family Contexts, and Broader Policies - Wodon, Quentin (Taylor and Francis, 2016)
Access to quality early childhood development (ECD), care, and pre-primary education is essential for child development and is now recognized as a priority under the Sustainable Development Goals. Investments in ECD by major donors have been rising rapidly in recent years. This makes the task of understanding better what works to promote ECD, and what may not work as well, a priority. The objective of this special issue of the Journal of Human Development and Capabilities is to contribute to the evidence base in three areas—the roles of program interventions, family contexts, and broader policies in ensuring optimal child development. The issue consists of five research articles, most of which provide evaluations of specific interventions, as well as three shorter notes considering broader policy issues. The main conclusions of the various contributions are summarized in this article together with a brief introduction to simple conceptual frameworks that countries, donors, and other stakeholders may find useful when considering alternative ways to invest in ECD.